(3CMcGe GdCHhjf ai Gdabg GdESdGei (B: s (3OQGSI ebGQfI (B/ s - (3CMeO eMehO eMeO YHOGdSdGes; (3YHOGdYRjR QeVGf Sec s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GbGgQI,s, 2019)
(3JfGhdJ GdOQGSI GMcGe GdCHhjf ai Gdabg GdESdGei cOQGSI ebGQfI Hjf GdePGgH GdCQHYI(B: (3GdMfajI h GdeGdcjI h GdTGaYjI h GdMfHdjI ai GHhGH Gdabg GdeNJdaI acGf GdHGH GdChd CdMcGe GdCHhjf ai GdYHGOGJ HJaUjd CfhGYgG ef YHGOGJ HOfjI h YHGOGJ eGdjI h YHGOGJ eGdjI HOfjI h JfGhd GdHGH GdKGfi GMcGe GdCHhjf ai GdeYGedGJ h Pdc HPcQ GMcGe GdCHhjf ai GdhGdjI Ydi GdeGd h GMcGe GdCHhjf ai GdeYGhVGJ h GMcGe GdCHhjf ai GdJHQYGJ h GMcGe GdCHhjf ai GdQgf h GdTaYI h GdVeGf h eOi LhGR CNP GdCH ef eGd GdCHf Ke GMcGe GCdHhjf ai GdejQGK h LGA GdHGH GdKGdK HYfhGf GMcGe GCdHhjf GdeJYdbI HCMcGe GCdSQI h JfGhd GMcGe GCdHhjf ai GdfcGM h GMcGe GCdHhjf ai aQb GdfcGM h GMcGe GCdHhjf ai GdfabI h GMcGe GdCHhjf ai GdfSH h GMcGe GdCHhjf ai GdQVGY h GMcGe GdCHhjf ai GdMVGfI h LGA GdHGH GdQGHY HYfhGf GMcGe GdCHhjf ai GdYbhHGJ h GdTgGOI h GdbVGA h JfGhd GMcGe GdCHhjf ai GdbUGU h GMcGe GdCHhjf ai LQGFe GdMOhO h GMcGe GdCHhjf ai YbhHI GdJYPjQ h GMcGe GdCHhjf ai GdTgGOI Ke CMcGe GdCHhjf GdbVGA h bO bGQfJ GdOQGSI GdbGfhf GdeUQi HGdabg GdESdGei ai GMcGe GdCHhjf h NdUJ Edi fJGFL h JhUjGJ JYdb HYVgG HVQhQI EbQGQ JYOjdGJ JTQjYjI dHYV GdeSGFd ai GdbGfhf GdeUQi JJYdb HCMcGe GdCHhjf MJi jhGab GdbGfhf eG SeJ Hg GdTQjYI GdESdGejI ai JfGhdgG CdMcGe GdCHhjfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejI, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B365-381s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdTQjYI GdESdGejIs; (3GMcGe GdCHhjf aj GdYHGOGJ GdHOfjIs; (3CMcGe GdCHhjf aj GdYHGOGJ GdeGdjIs; (3GSJFLGQ GdCHhjf hGdYcSs; (3CMcGe GdCHhjf aj GdYbhHGJ hGdTgGOI hGdbVGA s; (3EYaGa GdCHhjfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs